NEW SPECIES OF CROSSODACTYLUS (ANURA, LEPTODACTYLIDAE) FROM THE ATLANTIC RAIN-FOREST OF SOUTHEASTERN BRAZIL - Bastos, R. P.; Pombal, J. P. (Amer Soc Ichthyologists Herpetologists Business Office, 1995)
A new species of leptodactylid frog, Crossodactylus caramaschii, is described from the southern part of the state of São Paulo, southeastern Brazil. The new species, a member of the Crossodactylus gaudichaudii group, is characterized by having a short snout, a distinct and straight canthus rostralis, and reticulated belly.